STUDY AND CORRECTION OF MICROELEMENT IMBALANCE IN PATIENTS WITH GIARDIASIS - Duysenova Gulzar Karlibaevna, (TADQIQOTLAR, 2026)
Abstract Giardiasis  is  a  widespread  parasitic  disease  that  often  leads  to  chronic gastrointestinal  disorders,  malabsorption,  and  metabolic  disturbances.  One  of  the important  but  insufficiently  studied  consequences  of  giardiasis  is  the  imbalance  of essential microelements. The study included patients diagnosed with giardiasis based on parasitological and immunological tests. Serum levels of essential microelements were determined before and after treatment. Patients received standard antiparasitic therapy combined with microelement correction.